Transsynaptic Modulation of Kainate Receptor Functions by C1q-like Proteins. - Matsuda, K; Budisantoso, T; Mitakidis, N; Sugaya, Y; Miura, E; Kakegawa, W; Yamasaki, M; Konno, K; Uchigashima, M; Abe, M; Watanabe, I; Kano, M; et al. (Elsevier, 2016)
Postsynaptic kainate-type glutamate receptors (KARs) regulate synaptic network activity through their slow channel kinetics, most prominently at mossy fiber (MF)-CA3 synapses in the hippocampus. Nevertheless, how KARs cluster and function at these synapses has been unclear. Here, we show that C1q-like proteins C1ql2 and C1ql3, produced by MFs, serve as extracellular organizers to recruit functional postsynaptic KAR complexes to the CA3 pyramidal neurons. C1ql2 and C1ql3 specifically bound the amino-terminal domains of postsynaptic GluK2 and GluK4 KAR subunits and the presynaptic neurexin 3 containing a specific sequence in vitro. In C1ql2/3 double-null mice, CA3 synaptic responses lost the slow, KAR-mediated components. Furthermore, despite induction of MF sprouting in a temporal lobe epilepsy model, KARs were not recruited to postsynaptic sites in C1ql2/3 double-null mice, leading to reduced recurrent circuit activities. C1q family proteins, broadly expressed, are likely to modulate KAR function throughout the brain and represent promising antiepileptic targets.